EXOME SEQUENCING IN THREE FAMILIES WITH CYTOPLASMIC BODY MYOPATHY WITH EARLY RESPIRATORY FAILURE. (29th November 2012) - Chinnery, P; Pfeffer, G; Griffin, H; Elliott, H; Barresi, R; Straub, V; Udd, B; Horvath, R; Dick, D
Abstract : Introduction: Cytoplasmic body myopathy with early respiratory failure (CBM) is a rare muscular dystrophy with the clinical presentation of early respiratory failure with distal and/or proximal muscle weakness. The genetic defect has been identified in two families, having the R279W mutation in the sarcomeric protein TTN, although cases without this mutation have already been reported. Methods: Three pedigrees with CBM were included in this study. Clinical characteristics and diagnostic investigations were summarised. Western blot of C-terminal TTN protein was performed. Genome-wide 1000 microsatellite analysis was performed in one of the families to identify a linkage region and shared haplotype. Exome sequencing was performed on three patients. Results: Onset was usually in middle-age, and tibialis anterior muscle was earliest and most severely affected. Pulmonary function tests indicated low FEV1 and FVC, worsening when supine. EMG demonstrated necrotising myopathic process. MRI invariably revealed signal abnormalities of semitendinosus muscle. Blot of C-terminal TTN protein was normal. A 20 cM linkage region on chromosome 2 was identified. Exome sequencing detected the disease mutation and identified other candidates excluded with segregation analysis. Conclusions: We report the disease gene, and describe in detail the phenotype and diagnostic investigations from these three pedigrees. Genetic testing for these CBM genes should be performed in patients with myopathy and early respiratory failure if muscle pathology reveals cytoplasmic bodies or is nonspecific.